2020
DOI: 10.3389/fnbeh.2020.00045
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Ethanol Exposure: Anxiety-Like Behavioral Alterations, Ethanol Intake, and Sensitivity

Abstract: Adolescence is a developmental period associated with rapid age-specific physiological, neural, and hormonal changes. Behaviorally, human adolescents are characterized by age-typical increases in novelty-seeking and risk-taking, including the frequent initiation of alcohol and drug use. Alcohol use typically begins during early adolescence, and older adolescents often report high levels of alcohol consumption, commonly referred to as high-intensity drinking. Early-onset and heavy drinking during adolescence ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 107 publications
2
20
0
Order By: Relevance
“…2008 ). This relationship between adolescent and adult alcohol consumption has been found also in animal models ( Towner and Varlinskaya 2020 ).…”
Section: Introductionsupporting
confidence: 53%
See 2 more Smart Citations
“…2008 ). This relationship between adolescent and adult alcohol consumption has been found also in animal models ( Towner and Varlinskaya 2020 ).…”
Section: Introductionsupporting
confidence: 53%
“…2019 ). In contrast, as reviewed recently, approximately only a third of the studies using voluntary alcohol consumption models have been able to demonstrate increased alcohol intake when recorded later in adulthood ( Towner and Varlinskaya 2020 ). For example, intermittent 20% free-choice alcohol drinking by adolescent Wistar rats increased their alcohol consumption later in life ( Amodeo et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, even if human studies suggest that age of onset of alcohol use is associated with the risk to develop AUD later in life, recent systematic reviews suggest that this association is less consistent and might be driven by confounding factors, such as the history of alcohol problems in the family, preceding mental health problems, socioeconomic status, or genetic background ( Maimaris and McCambridge, 2014 ; Marshall, 2014 ; Kuntsche et al, 2016 ). Even animal studies on this issue are not always consistent ( Labots et al, 2018 ; Spear, 2018 ; Towner and Varlinskaya, 2020 ; Mugantseva et al, 2021 ) and therefore, further investigation is needed to help in clarifying the role of causality between early alcohol onset and increased risk of later AUD.…”
Section: Introductionmentioning
confidence: 99%
“…Using ethanol CTA, rodent studies have reliably demonstrated that adolescents are less sensitive to the aversive effects of ethanol as compared to adults [ 257 , 258 , 259 , 260 , 261 , 262 , 263 ]. In addition, animals exposed to ethanol as adolescents become relatively insensitive to the aversive effects of ethanol as adults [ 264 , 265 , 266 , 267 , 268 ]. Together, these findings suggest that exposure to ethanol during adolescence induces long-lasting decreases in sensitivity to the adverse effects of ethanol and may enable increased ethanol consumption, thus putting individuals at risk for the development of an AUD.…”
Section: Alcohol Sensitivity In Rodentsmentioning
confidence: 99%